Confirmation of Trachischium guentheri (Serpentes: Colubridae) from Tibet, China, with description of Tibetan T. monticola - Wang, Kai; Jiang, Ke; Jin, Jieqiong; Liu, Xu; Che, Jing (Zootaxa, 2019)
Little is known about the worm-eating snakes of the genus Trachischium in the East Himalaya due to their secretive nature. To date, only T. monticola and T. tenuiceps are recorded from China, and the former species was recorded based on historical literature without vouchered information. In addition, a questionable record of T. guentheri in Tibet, China exists in literature, but no one has yet confirmed this distribution record. Here we confirm the distribution of T. guentheri in southeastern Tibet, China based on a newly collected specimen, and provide the first detailed description of T. monticola, including the first description of its hemipenial morphology, based on newly collected Tibetan specimens. Lastly, we provide a diagnostic key to the three Chinese species, and discuss the general distribution patterns of the genus in the Trans-Himalayan Region.